Dissecting Cellular Heterogeneity Based on Network Denoising of scRNA-seq Using Local Scaling Self-Diffusion - Duan, Xin; Wang, Wei; Tang, Minghui; Gao, Feng; Lin, Xudong (Frontiers in Genetics, 2022)
Identifying the phenotypes and interactions of various cells is the primary objective in cellular heterogeneity dissection. A key step of this methodology is to perform unsupervised clustering, which, however, often suffers challenges of zero count observations and high level of noise, as well as high dimensionality. To overcome the limitations, we proposed self-diffusion on local scaling affinity (LSSD) to enhance cell similarities metric learning for dissecting cellular heterogeneity. Local scaling infers the self-tuning of cell-to-cell distances that are used to construct cell affinity. Our approach implements the self-diffusion process by propagating the affinity matrices to further improve the cell similarities for the downstream clustering analysis. To demonstrate the effectiveness and usefulness, we applied LSSD on simulated data and three real scRNA-seq datasets. Comparing with other single-cell clustering methods, our approach demonstrates much better clustering performance and cell types identified on colorectal tumors reveal strongly biological interpretability.